Cytoskeletal polarization plays a direct role in Drosophila testis niche assembly - Rhymer, Everette Martin Hanson (East Carolina University)
To retain their undifferentiated state, stem cells rely on self-renewal signals from their cellular microenvironment, the niche. A functional niche is often assembled in a specific tissue region to limit renewal signals to a select number of stem cells. Studying how niche assembly is coordinated with organogenesis is imperative to understanding regulation of tissue homeostasis and regeneration. We leverage the Drosophila testis to investigate development of its niche. Prior to niche assembly, the embryonic male gonad is a spherical arrangement of germ cells interspersed with somatic cells, a subset of which are specified as pro-niche cells. During assembly, pro-niche cells migrate to the outer edge of the gonad, and then to the anterior, where they cluster into a smooth, circular niche (Anllo et al., 2019). An unassembled niche cannot signal properly to GSCs. It is therefore crucial to understand mechanisms that underly niche formation. We previously showed that niche assembly requires niche cell accumulation of the transcription factor Islet, which is required for niche cells to polarize their cytoskeleton (Anllo & DiNardo, 2022). What remains elusive is whether F-actin directly mediates assembly, and what specific regulators of F-actin are required for the assembly process. We have established a method that employs molecular optogenetics to manipulate F-actin regulatory mechanisms during specific stages of niche ii development. Here, we demonstrate precise temporal control of the Cry2 CIBN system in the embryonic testis, using blue light to direct localization of cytoskeletal modulators to the cell cortex. Using in vivo live imaging with these optogenetic techniques, we show a direct role for polarization of cortical F-actin in niche assembly. Our data support a requirement for the cytoskeletal modulator Rho1 in enabling niche cells to accumulate adhesion proteins and assemble with the proper architecture. Together, our work defines direct contributions of the F-actin cytoskeleton in establishment of a stem cell niche.
Keywords: Biology, Molecular